Standard medical nutrition therapy of 25 kcal/kg ideal bodyweight/day often does not reach even resting energy expenditure for patients with type 2 diabetes. Issue 3 (28th November 2019) - Fukuda, Takuya; Tanaka, Muhei; Yamazaki, Masahiro; Marunaka, Yoshinori; Fukui, Michiaki
Abstract: Aims/Introduction: In Japan, an ideal bodyweight (IBW) calculated by 22 × height (m) 2 has commonly been used in the planning of medical nutrition therapy (MNT). However, there have been concerns regarding calorie deficits in fulfilling resting energy expenditure (REE) for patients with type 2 diabetes undergoing MNT as defined by 25 kcal/kg IBW/day. The objective of the present study was to measure REE in patients with type 2 diabetes and verify the validity of MNT with 25 kcal/kg IBW/day. Materials and Methods: A retrospective cross‐sectional study was carried out in 52 patients with type 2 diabetes (mean age was 65.9 ± 7.3 years, bodyweight 65.0 ± 11.3 kg, body mass index 24.9 ± 3.8 kg/m 2 ). REE was measured by indirect calorimetry. Results: The mean REE was 1, 601.0 ± 253.1 kcal/day. Assuming that all patients strictly observed daily energy intake as 25 kcal/kg IBW/day, 41 of 52 patients (78.9%) did not reach their REE. The greater the bodyweight, the greater the difference between assumed energy intake as 25 kcal/kg IBW and REE. Conclusions: We call attention to the potential risk of total dietary energy intake set to 25 kcal/kg IBW/day. Clinicians should carefully plan MNT to not fall below a patient's REE to prevent sarcopenia and ensure MNT continuity. Abstract : Assuming that all patients with type 2 diabetes strictly observed daily energy intake as 25 kcal/kg ideal bodyweight/day, 41 of 52 patients (78.9%) did not reach their REE. The greater the bodyweight, the greater the difference between assumed energy intake as 25 kcal/kg ideal bodyweight and REE.